Nigella sativa: A Dietary Supplement as an Immune-Modulator on the Basis of Bioactive Components - Niu, Yun; Wang, Baoguang; Zhou, Li; Ma, Changyang; Waterhouse, Geoffrey I. N.; Liu, Zhenhua; Ahmed, Adel F.; Sun-Waterhouse, Dongxiao; Kang, Wenyi (Frontiers in Nutrition, 2021)
Nutrients can be considered as functional foods, which exert physiological benefits on immune system. The seeds of Nigella sativa, which have many active constituents, are mainly used for medicine, food spice, and nutritional supplements in Egypt. Much attention has been paid to N. sativa seeds for their anticancer, antibacterial, anti-inflammatory, and immune properties. However, their active constituents and mechanisms underlying functions from N. sativa seeds is unclear. Thus, the bioactive constituents with immune regulation in N. sativa seeds were systematically studied. A new compound (3-methoxythymol-6-O-β-D-apiofuranosyl-(1→6)-β-D-glucopyranoside 1) and 11 known compounds (2–12) were separated from the N. sativa seeds by chromatographic methods. Their structures were then elucidated by spectroscopic analysis of MS, UV, IR, 1H-, and 13C-NMR. Furthermore, immunomodulatory effects of those compounds in RAW 264.7 cells were evaluated by phagocytosis, nitric oxide (NO) and cytokine release, related mRNA transcription, and key proteins expression in vitro. Monosaccharide derivatives, Ethyl-α-D-furaarabinose (5), and Ethyl-β-D-fructofuranoside (8) were shown to played bidirectional regulatory roles in immunity and anti-inflammation through the regulation of nuclear factor-κB (NF-κB) signaling pathways. The results showed the active compounds and mechanisms of immune regulation in N. sativa, thus indicating that N. sativa seeds could be used as dietary supplements in immunomodulation.